UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK HERBA ALFALFA (Medicago sativa L.) DENGAN METODE DPPH (1,1-difenil-2-pikrilhidrazil) - herni widyowati; Maria Ulfah; sumantri sumantri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACT Alfalfa (Medicago Sativa L.) plant is known to have compounds of flavonoid and vitamine C which can serve as antioxidants. This research aims knowing the antioxidant activity of alfalfa herbal ethanolic extract using DPPH (1,1-diphenyl-2-pikrilhydrazil method and knowing the content of its active compound have wan. The research was performed by making alfalfa herbal ethanolic extract by maceration method using ethanol extracting solvent 70%. The extract was divided into some concentrations of 10, 20, 40 and 80 μg/ml. As a comparison, vitamine C was used with concentrations of 1, 2, 4, and 8 μg/ml. The test of antioxidant activity was conducted by reacting 50 μl of alfalfa herbal ethanolic extract with 4.0 ml DPPH 0.1 mM, then it was measured for the absorbance using visible spectrophotometry with a wavelength of 525 nm. The obtained data was calculated to discover its antioxidant activity. The statistical analysis used was Mann-Whitney test. The IC50 value was gained using probit analysis and the statistical analysis used t-test and to discover the content of active compound in alfalfa herbal ethanolic extract, TLC test was performed. The research result indicated that the alfalfa herbal ethanolic extract had antioxidant activities with alfalfa herbal ethanolic extract IC50 value of 59.339 μg/ml, and standard solution of vitamine C IC50 value of 4.768 μg/ml. The result of statistical test for IC50 indicated an unsignificant difference between alfalfa herbal ethanolic extract and vitamine C. Otherside it could be concluded that the alfalfa herbal ethanolic extract containing flavonoid had antioxidant activities. Keywords: Alfalfa (Medicago sativa L.) herbal ethanolic extract, IC50, antioxidant